Unraveling immortality and the genesis of human soul in st. Augustine’s selected works - Warchał, Robert Artur (Humaniora. Czasopismo Internetowe, 2023)
The article intends to explore topics concerning the eternal nature and the origin of the human soul. Augustine’s ontological perspective on humanity upholds the truth of its existence. In ancient philosophy and Christian theology, the doctrine of the immortality of the soul and its origin has been an ongoing area of interest and debate. Saint Augustine, one of the most important theologians and philosophers in the history of the Catholic Church, addressed this issue in his works, considering both philosophical and theological aspects of the existence of the human soul. The author justifies his views by referring to the Holy Bible and to the vital functions of man. Also, he points to the dissimilarity between sensual and mental cognition. As part of its consideration, it relies on the Latin phrase anima rationalis which refers to the rational soul (animus). What speaks for immortality of the soul is the argument of evidence of the lack of a quantitative element, as well as the concepts of truth and life. The foregoing command gives grounds to believe that a human being remains a unique whole of physical and spiritual unity. Also, one of the the key thinks is the certainty of self-knowledge derived from the continuation of gnoseology, which proves that humans are capable of reflective, mind and abstract thinking, and the cognitive activity of the soul shows the ability to transcend the mortal body. This approach does provide a deeper understanding of the role of the soul in human life and in the context of eternity, an important topic in Christian theology and philosophy.